The Crux - Gilman, Charlotte Perkins (Saga Egmont, 2022)
Long out of print, Charlotte Perkins Gilman's novel The Crux is an important early feminist work that brings to the fore complicated issues of gender, citizenship, eugenics, and frontier nationalism. First published serially in the feminist journal The Forerunner in 1910, The Crux tells the story of a group of New England women who move west to start a boardinghouse for men in Colorado. The innocent central character, Vivian Lane, falls in love with Morton Elder, who has both gonorrhea and syphilis. The concern of the novel is not so much that Vivian will catch syphilis, but that, if she were to marry and have children with Morton, she would harm the "national stock." The novel was written, in Gilman's words, as a "story . . . for young women to read . . . in order that they may protect themselves and their children to come." What was to be protected was the civic imperative to produce "pureblooded" citizens for a utopian ideal. Dana Seitler's introduction provides historical context, revealing The Crux as an allegory for social and political anxieties-including the rampant insecurities over contagion and disease-in the United States at the beginning of the twentieth century.